Effects of converting secondary tropical peat swamp forest into oil palm plantation on soil chemical properties in Sibu, Sarawak - Salimin, Muhamad Ismawi (2016)
Malaysia is among the largest oil palm producer in the world. High demand of palm oil industry, lead to the land clearing for oil palm plantations. However, excessive land clearing destroys fragile ecosystem of unique flora and fauna biodiversity especially peat swamp forests. In general, various activities involved when peat swamp forest cleared into oil palm plantation e.g., timber harvesting, drainage, land clearing, biomass, waste management, earthworks, planting and replanting. These activities affect chemical properties of soil, which can’t be avoided during conversion. To understand those chemical changes, a study was carried out to determine the effect of converting secondary tropical peat swamp forest (TPSF) into oil palm plantation on selected soil chemical properties. This study was conducted in secondary TPSF in Sibu, Sarawak, Malaysia. The soil samples were taken in 3000 m2 of experimental plot which were set up in secondary TPSF before and after timber harvesting, secondary TPSF has been drained and cleared land, two and three years old of young oil palm plantation (YOPP) and mature oil palm plantation (MOPP). The peat soils were sampled randomly using a peat auger at standard depth (0 cm to 15 cm) and labelled. A total of 48 samples for each site were taken at each corner and the middle of a plot. Samples were then air-dried at room temperature, homogenized and sieved for further analysis. Soils chemical properties i.e., soil acidity, cation exchange capacity (CEC), soil organic matter (SOM), total carbon, total nitrogen, total phosphorus, total potassium and exchangeable potassium (K) were determined using standard laboratory procedures. The alterations of secondary TPSF to agriculture begin with logging activities. Therefore, the first part of this study was to determine the comparison of selected chemical properties of peat swamp soil before and after timber harvesting. Throughout this study, it showed there were significant difference on selected soil chemical properties before and after logging e.g., soil pH H2O, CEC, SOM, total carbon, total nitrogen, total phosphorus and exchangeable K. Soil pH KCl and C:N ratio showed there were no significant changes. During the land clearing, soil nutrients and chemical properties changes as land converted into agriculture or for urbanization. Therefore, the second part of the study was to determine the effect of land clearing on selected soil major macro-nutrient and other selected chemical property of secondary TPSF. This study showed there were significant difference of soil chemical properties such as decreasing of soil pH H2O, CEC, SOM, total carbon, total nitrogen, total phosphorus, total potassium and C:N ratio. However, there were increases in soil pH KCl and C:P ratio. After clearing land of the secondary TPSF, peat soil chemical properties continue to change as land preparation and application of fertilizer activities for oil palm planting. Therefore, the third part of the study was to determine the effect of cultivation at different age’s oil palm plantation on selected chemical properties. This study, showed there were no significant different in CEC, total carbon and SOM. Otherwise for soil pH showed significantly difference from each other by YOPP (three years) the lowest and MOPP the highest. In total N, YOPP (three years) showed significantly the highest, followed by MOPP and YOPP (two years) was the lowest. While for total phosphorus, both YOPP (two years) and MOPP share significant higher compare to YOPP (three years). Total potassium, MOPP showed significantly highest compared to both YOPP. For C:N and C:P ratio there were mixed significant different by YOPP (two years) was the highest in C:N ratio and YOPP (three years) highest in C:P ratio. For conclusion, the chemical properties of peat soil reacted to the changes that occur during land clearing, drainage, and planting process as peat soil undergoing a degradation process. Beside the negative impact of timber harvesting operation to secondary TPSF soil, there were also several positive impacts on harvesting operation in terms of nutrients such as increasing of total nitrogen, total phosphorus and available potassium in peat swamps forest soil. The common effect of logging and land clearing in the peat soil are lost of carbon storage to the atmosphere and changing in soil chemical properties, removal of plants that responsible in maintaining the balance of the carbon cycle in peat soil. Consequently, alteration of secondary TPSF for agriculture purpose was one of the causes in increasing the earth temperature and global warming. Conversion into oil palm plantation has disturb the chemical properties of peat soil e.g., application of lime and fertilizer especially NPK fertilizer. For recommendation, changes of peat soil chemical properties should be also observed with soil physical properties and good management of land clearing should minimize the degradation of peat soil.